Medication adherence and complementary therapy usage in inflammatory bowel disease patients during the coronavirus disease 2019 pandemic. Issue 5 (29th March 2021) - Barnes, Alex; Andrews, Jane; Spizzo, Paul; Mountifield, Réme
Abstract: Background and Aim: Medication nonadherence is common in patients with inflammatory bowel disease (IBD) and has been associated with worse outcomes. The coronavirus disease 2019 (COVID‐19) pandemic led to significant consumer and medical concern regarding the possible risks of immunosuppressive medications during the pandemic. This study aimed to examine medication adherence and complementary and alternative medicine (CAM) usage during the COVID‐19 pandemic. Methods: An online survey was sent to patients from two tertiary IBD units. The survey included medication nonadherence attributed to the COVID‐19 pandemic, complementary therapy, and IBD medication use. Validated measures of IBD disease activity, medication adherence, and beliefs about medicines were obtained. Results: Of 262 respondents (median age of 46, 58% female) 14 (5%) patients reported self‐initiated missed doses or dose reduction of IBD medications directly attributed to the COVID‐19 pandemic. Positive associations with medication nonadherence included current corticosteroid requirement ( P  = 0.022), higher disease activity scores ( P  = 0.026), and higher concern about medicines score ( P  = 0.04). CAM usage was common, aimed at treating mental health in most cases, and infrequently attributed to the COVID‐19 pandemic. Conclusions: Even in the setting of low COVID‐19 prevalence, the pandemic reduced IBD medication adherence in 1 in 20 patients. This reduced adherence was co‐associated with increased disease activity and corticosteroid use. Understanding the underlying beliefs driving suboptimal IBD medication adherence is critical to prevent avoidable adverse IBD outcomes. Abstract : The coronavirus disease 2019 (COVID‐19) pandemic resulted in widespread concern that inflammatory bowel disease (IBD) medications may result in higher infection risk and poor outcomes. The rate of medication nonadherence attributed to the COVID‐19 pandemic in an Australian IBD population was low and associated with increased IBD disease activity, corticosteroid use, and patient concern over medications. Understanding the underlying beliefs driving suboptimal IBD medication adherence is critical to prevent avoidable adverse IBD outcomes.